Um experimento para determinação da velocidade do som em barras metálicas - (:unkn) unknown (Universidade Federal do Pampa, 2019)
The present work proposes the creation of a resource for the study of mechanical waves, sound propagation in conductive solid media, aiming at its use in high school as an experimentation tool for teaching. It is believed that this experiment has the potential to motivate and assist students in better understanding this content, this feature uses a simple ratio between distance and propagation time, making it more understandable. The experimental apparatus developed during the research project proved to be potentially valid for the study of mechanical waves and their propagation in the media. The apparatus uses materials found in the domestic market, making its reproduction accessible.
Keywords: Experimentação; Plataforma Arduino; Ondas mecânicas; Velocidade do som; Arduino platform; Physics teaching; Mechanical waves; Speed of sound; CNPQ::CIENCIAS EXATAS E DA TERRA